Silent Cerebral Events/Lesions Related to Atrial Fibrillation Ablation: A Clinical Review. (11th February 2015) - DENEKE, THOMAS; JAIS, PIERRE; SCAGLIONE, MARCO; SCHMITT, RAINER; DI BIASE, LUIGI; CHRISTOPOULOS, GEORGIOS; SCHADE, ANJA; MÜGGE, ANDREAS; BANSMANN, MARTIN; NENTWICH, KARIN; MÜLLER, PATRICK; KRUG, JOACHIM; et al.
Silent Cerebral Events/Lesions Related to AF Ablation: Brain magnetic resonance imaging (MRI) has identified a high incidence of cerebral ischemia in asymptomatic patients after atrial fibrillation (AF) ablation (silent). Detection of cerebral ischemic events on MRI is based on acute hyperintense lesions on diffusion‐weighted imaging. In the literature, the incidence is related to specifications of MRI and depends on the definition applied. In comparative studies, silent cerebral events (SCE, diffusion‐weighted MRI [DWI] positive only) appear to be approximately 3 times more common compared to using a definition of silent cerebral lesions (SCL; without fluid attenuated inverse recovery sequence [FLAIR] positivity). Whereas the FLAIR sequence may turn positive within days after the ischemic event, SCE definition is highly sensitive for early phases of ischemic brain damage. SCE/SCL appear to represent cerebral ischemic infarcts and determine the "embolic fingerprint" of a specific ablation technology and strategy used. The optimum time point for detecting SCE is early after AF ablation (24–72 hours), whereas detection of SCL can only be performed within the first 2–7 days (due to delay of FLAIR positivity). Different technology‐, procedure‐, and patient‐related parameters have been identified to play a role in the multifactorial genesis of SCE/SCL. In recent years, evidence has been gathered that there may be differences of SCE/SCL rates depending upon the ablation technology used, but small patient numbers and a large number of potential confounders hamper all studies. As major findings of recent studies, mode of periprocedural and intraprocedural anticoagulation has been identified as a major predictor for incidences of SCE/SCL. Whereas procedural characteristics related to higher SCE/SCL‐rates may be modified, unchangeable patient‐related factors should be taken into account for future individualized risk assessment. Novel ablation devices introduced into the market should be tested for their potential embolic fingerprint and refinements of ablation procedures to reduce their embolic potential should be prompted. The knowledge of "best practice" in terms of low SCE/SCL rates has prompted changes in work‐flow, which have been implemented into ablation procedures using novel ablation devices. So far, no study has linked SCE/SCL to neuropsychological decline and the low number of AF‐ablation‐associated events needs to be weighted against the multitude of preexisting asymptomatic MRI‐detected brain lesions related to the course of AF itself. Future studies are needed to evaluate if more white matter hyperintensities due to AF may be prevented by AF ablation (producing only a small number of SCE/SCL).